The Arabidopsis Transcription Factor CDF3 Is Involved in Nitrogen Responses and Improves Nitrogen Use Efficiency in Tomato - Domínguez-Figueroa, José; Carrillo, Laura; Renau-Morata, Begoña; Yang, Lu; Molina, Rosa-V; Marino, Daniel; Canales, Javier; Weih, Martin; Vicente-Carbajosa, Jesús; Nebauer, Sergio G.; Medina, Joaquín (Frontiers in Plant Science, 2020)
Nitrate is an essential macronutrient and a signal molecule that regulates the expression of multiple genes involved in plant growth and development. Here, we describe the participation of Arabidopsis DNA binding with one finger (DOF) transcription factor CDF3 in nitrate responses and shows that CDF3 gene is induced under nitrate starvation. Moreover, knockout cdf3 mutant plants exhibit nitrate-dependent lateral and primary root modifications, whereas CDF3 overexpression plants show increased biomass and enhanced root development under both nitrogen poor and rich conditions. Expression analyses of 35S::CDF3 lines reveled that CDF3 regulates the expression of an important set of nitrate responsive genes including, glutamine synthetase-1, glutamate synthase-2, nitrate reductase-1, and nitrate transporters NRT2.1, NRT2.4, and NRT2.5 as well as carbon assimilation genes like PK1 and PEPC1 in response to N availability. Consistently, metabolite profiling disclosed that the total amount of key N metabolites like glutamate, glutamine, and asparagine were higher in CDF3-overexpressing plants, but lower in cdf3-1 in N limiting conditions. Moreover, overexpression of CDF3 in tomato increased N accumulation and yield efficiency under both optimum and limiting N supply. These results highlight CDF3 as an important regulatory factor for the nitrate response, and its potential for improving N use efficiency in crops.